The Monopoly Game Improves Cognitive Skills in Children Aged Five to Six: Permainan Monopoly Meningkatkan Keterampilan Kognitif pada Anak Usia Lima hingga Enam Tahun - Ayulia dade; Choirun Nisak Aulina (Academia Open, 2025)
Early childhood education emphasizes play-based learning as a foundation for intellectual development (General Background). However, observations in Group B of Al-Faqih Islamic Kindergarten revealed low symbolic thinking skills, particularly in recognizing, using, and matching number symbols among children aged 5–6 years (Specific Background). Although educational games are widely recommended, limited classroom-based evidence documents structured board-game implementation for improving early cognitive competencies (Knowledge Gap). This study aimed to examine the use of a modified Monopoly game to develop cognitive abilities in young children (Aims). Using classroom action research with the Kemmis and McTaggart model, data were collected from 16 learners through observation, interviews, and documentation across two cycles. Achievement increased from 31% in the pre-cycle to 56% in Cycle I and reached 87% in Cycle II, surpassing the predetermined success indicator of 75% (Results). The study introduces an age-adapted Monopoly format integrating counting, sequencing, and symbol matching tasks within gameplay (Novelty). These findings suggest that structured board games can serve as practical instructional media to support symbolic reasoning and numeracy readiness in early childhood settings (Implications). Highlights: Learning progress rose steadily across intervention stages, culminating above the target threshold. Play sessions incorporated number recognition, ordering, and correspondence activities. High learner engagement accompanied the observed developmental gains. Keywords: Monopoly Game; Cognitive Development; Early Childhood Education; Symbolic Thinking; Classroom Action Research